Bio-alcohol production from anaerobic digestion of banana peels / Radzi M.E.A ...[et al.] - Radzi, M.E.A; Roslan, M.R.; Anuar, N.N; Elham, O.S.J
Bio-alcohol production from banana peels through the process of anaerobic digestion are one of many alternatives in producing renewable energy and at the same time reducing environmental effects. Bio-alcohol can be obtained by subjugating biomass through a series of pre-treatment processes to obtain the maximum amount of bio-alcohol. This experiment discuss the potential of biomass product as an alternative energy sources while at the same time producing clean and sustainable energy. Throughout the experiment, parameters such as temperature, pH and concentration of bio-alcohol that are produced are monitored. The composition of bio-alcohol was analyzed using the UV-Vis Spectrophotometry. The banana peels were separated to categories depending on the pre-treatment methods that were applied. The experiment was conducted under mesophilic conditions and at a pH range of 6.5 until 7.9 within 28 days of retention time. The highest result recorded in the experiment is when the banana peels undergo alkaline pre-treatment whereby bio-ethanol produced is 60.70 % and the second one being those that went through acidic pretreatment at 54.90% of bio-ethanol. The correlation of temperature, pH and retention time were important factors in an anaerobic process to ensure the conditions for the microorganisms to grow.